THE EFFECT OF STORE ATMOSPHERE AND WORD OF MOUTH ON THE DECISION TO VISIT RUFI COFFEE, DEWANTARA DISTRICT, NORTH ACEH REGENCY - Era Fazira; Agustinawati; Riyandhi Praza; Sufi; Nanda Ameliany (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to examine the effect of store atmosphere and word of mouth on visiting decisions at Rufi Coffee, Dewantara District, North Aceh Regency. The study was motivated by the rapid growth of coffee shops, which has intensified competition among cafes, encouraging business owners to create a comfortable store atmosphere and foster positive word of mouth. This research employed a quantitative method with an associative approach, and the data were analyzed using multiple linear regression. The sample consisted of 100 respondents selected using the Lemeshow formula. Data were collected through a Likert-scale questionnaire that had passed the validity and reliability tests. The findings indicate that store atmosphere and word of mouth have a positive and significant effect on visiting decisions. The t-test results show that the t value for store atmosphere was 4.322 and for word of mouth was 8.509, both exceeding the t-table value of 1.985, with a significance value of 0.000 < 0.05. The F-test yielded an F value of 186.293 with a significance value of 0.000 < 0.05. The coefficient of determination (R²) was 0.793.